2022
DOI: 10.1111/ctr.14838
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary feasibility of animated video education designed to empower patients’ referral to kidney transplantation

Abstract: Background: Referral for kidney transplantation is influenced by patient education; digital technologies can enhance broad information accessibility. This single-group study tested the feasibility and acceptability of patient-centered self-directed educational animated videos to improve mediators of kidney transplant referral. Methods: Community-based adults with chronic kidney disease stage ≥4 invited from a clinical registry or self-responding to flyers viewed eight sequential videos (19:36 min total duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The findings of the current study revealed that the majority of the studied patients have satisfaction regarding using multimedia and stated that multimedia was useful, interactive while only (18.3%) did not report satisfaction regarding multimedia. this finding was parallel with a study applied by Eneanya et al,(2020) (36) for using of a Supportive Kidney Care Video Decision in older patients and the results indicated that patients who received video education reported high satisfaction and acceptability ratings. Our study results also match with a study conducted by Kayler et al .,(2023) (37) who found that animated video education is promising to improve diverse individuals' knowledge, ease of learning concerns, and Vol.…”
Section: Concerningsupporting
confidence: 85%
“…The findings of the current study revealed that the majority of the studied patients have satisfaction regarding using multimedia and stated that multimedia was useful, interactive while only (18.3%) did not report satisfaction regarding multimedia. this finding was parallel with a study applied by Eneanya et al,(2020) (36) for using of a Supportive Kidney Care Video Decision in older patients and the results indicated that patients who received video education reported high satisfaction and acceptability ratings. Our study results also match with a study conducted by Kayler et al .,(2023) (37) who found that animated video education is promising to improve diverse individuals' knowledge, ease of learning concerns, and Vol.…”
Section: Concerningsupporting
confidence: 85%
“…Our research group recently developed a curriculum of educational animations (named KidneyTIME) to promote kidney transplant access, which has been previously described [ 27 ]. The need for additional information regarding kidney transplant complications was noted during development studies with patients [ 28 ] and interviews with lay caregivers [ 15 ]. Specifically, patients and families assessing kidney transplant educational materials felt unprepared for transplant complications and desired more information about kidney transplant risks, specifically in video format [ 15 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The need for additional information regarding kidney transplant complications was noted during development studies with patients [ 28 ] and interviews with lay caregivers [ 15 ]. Specifically, patients and families assessing kidney transplant educational materials felt unprepared for transplant complications and desired more information about kidney transplant risks, specifically in video format [ 15 , 28 ]. Therefore, our research team developed a pair of videos about common kidney transplant complications to improve the balance of the content within the KidneyTIME curriculum and to improve kidney transplant preparedness.…”
Section: Introductionmentioning
confidence: 99%